PENGARUH PEMBERDAYAAN PSIKOLOGIS, KEPUASAN KERJA DAN KOMITMEN AFEKTIF TERHADAP KINERJA PEGAWAI PT. PERTAMINA UNIT PEMASARAN I CABANG BANDA ACEH - Hamdi Harmen; Karlina Yulia Ningsih (JURISMA : Jurnal Riset Bisnis & Manajemen, 2014)
The purpose of this study was to determine the effect of psychological empowerment, job satisfaction and affective commitment to the performance of the employees of PT. Pertamina Marketing Unit I Branch of Banda Aceh with a total sample of 69 respondents. Primary data were collected by distributing sheets of questions (questionnaire). Analytical equipment used is multiple linear regression method and which is the object of this research is psychological empowerment, job satisfaction, affective commitment, and employee performance at PT. Pertamina Marketing Unit I Branch of Banda Aceh. While the sampling is done by census method, which means using the entire population as a source of data or a sample in which the samples were taken are all employees working in PT. Pertamina Marketing Unit I Branch of Banda Aceh. The results showed that simultaneous Fcount > Ftable, thus it can be concluded that the alternative hypothesis (Ha) proposed is acceptable and the null hypothesis (Ho) is rejected, it means that psychological empowerment (X1), job satisfaction (X2), and affective commitment (X3) significantly affect the performance of employees at PT. Pertamina Marketing Unit I Branch of Banda Aceh with a correlation coefficient (R) of 0.812 which shows that there is a strong relationship between the three independent variables with the performance of employees at PT. Pertamina Marketing Unit I Branch of Banda Aceh, while the coefficient of determination (R2) in this study was obtained 0.660 which illustrates that the three independent variables affect the performance of employees at PT. Pertamina Marketing Unit I Branch of Banda Aceh at 66.0%.Keywords: Psychological Empowerment, Job Satisfaction, Affective Commitment and Employee Performance